Hubungan antara Kesadahan Air Minum, Kadar Kalsium dan Sedimen Kalsium Oksalat Urin pada Anak Usia Sekolah Dasar - M. Dody Izhar, Haripurnomo K, Suhardi Darmoatmodjo (Berita Kedokteran Masyarakat (BKM), 2007)
Background: Water hardness containing calcium mineral (Ca2+) is supposed to increase absorption in intestinal lumen and calcium excretion (hyper-calciuria) of urine. Alkalic conditioned urine can cause changes of saturation concentration to become calcium supersaturation leading to the crystalization of calcium oxalate.Objective: To identify the relationship between drinking water hardness, drinking and eating habit to calcium level and urine calcium oxalate sediment.Method: The study was observational with cross sectional design. Examination analysis of drinking water hardness (mg/l), level of urine calcium (mg/dl) and calcium oxalate sediment of first/morning urine samples of 128 elementary school students (6-12 years old) was carried out using one-stage cluster random sampling technique at Sidowangi Subdistrict of Kajoran, District of Magelang, Central Java. Data of drinking and eating habit for bestial protein, vegetable protein, calcium and phospor, uric acid, oxalic acid and citric acid of the subject of the study were obtained from interview using questionnaires and food frequency forms. Data analysis used Stata version 8.0 program for windows at significance level. p<0.05.Result: Ave0rage value and main deviation of drinking water hardness was 66.75 + 8.36, level of urine was 10.43 + 6.40 and there were 52 subjects (40.63%) with calcium oxalate crystal. The result of statistical analysis showed that drinking water hardness did not affect level of urine calcium (rs =0.004; p=0.967; POR=1,017; 95% CI=0.476-2.172) and calcium oxalate sediment (rs=-0.007; p=0.937; POR=0.972; 95% CI= 0.480-1,969). Drinkinghabit (p=0.007; POR=3.509; 95% CI=1.339-8.802) and eating habit of citric acid sources (adequate p=0.066; POR=3.037; 95%CI=0.931-9,903, less p=0.000; POR=10,996; 95% CI=3.533-34.218) were 2 predisposition variables of calcium oxalate sediment status.Conclusion: Drinking water hardness had no effect to level of urine calcium and calcium  oxalate sediment. Drinking habit and eating habit for citric acid sources were 2 most determining factors, i.e. as protection or inhibitor of calcium oxalate crystalization formation.Keywords: water hardness, calcium level, calcium oxalate sediment